Acute pancreatitis in elderly patients: a single-center retrospective evaluation of clinical outcomes. (3rd April 2019) - Quero, Giuseppe; Covino, Marcello; Fiorillo, Claudio; Rosa, Fausto; Menghi, Roberta; Simeoni, Benedetta; Potenza, Annalisa; Ojetti, Veronica; Alfieri, Sergio; Franceschi, Francesco
Abstract: Introduction: Acute pancreatitis (AP) incidence in the elderly population has increased in the last years. However, the role of age as influencing factor on the AP clinical course is still debated. Methods: We reviewed clinical records of consecutive patients admitted with diagnosis of AP. Patients were divided in elderly (≥65 years) and non-elderly  (<65 years). Primary endpoint was comparison of overall mortality. Secondary endpoint included ICU admission, in-hospital length of stay (LOS) and surgical procedures. Results: We enrolled 352 elderly and 532 non-elderly patients. A higher mortality rate (7.4% vs 1.9%; p  < .001), ICU admission rate (18.9% vs 6.3%; p  < .001) and prolonged length of hospital stay (9 (6–14) vs 7 (5–11.7) days; p  = .01) were registered in the ≥65 years group. Multivariate analysis identified age (OR: 3.5; 95% CI:1.645–7.555; p  = .001), a higher Ranson score at admission (OR: 5.52; 95% CI:1.11–27.41; p <.001) and necrotic pancreatitis (OR: 8.6; 95% CI:2.46–30.27; p  = .001) as independent predictors of mortality. Conversely age and necrotic pancreatitis were independent risk factors for higher LOS and ICU admission. Conclusions: Patients with AP and age ≥65 years have a higher mortality, ICU admission and prolonged LOS. Early recognition and prompt treatment are key elements to improve outcomes in this population.